Plasmablastic pituitary lymphoma in a patient with human immunodeficiency virus: brief review of the literature and clinical case report - D. V. Martynov; T. T. Valiev; A. A. Odzharova; Yu. E. Ryabukhina; P. A. Zeynalova; S. N. Mikhailova (Онкогематология, 2024)
Plasmoblastic lymphoma is a rare, aggressive B-cell malignancy with poor long-term survival. Plasmoblastic lymphoma occurs most commonly in patients infected with human immunodeficiency virus (HIV), but cases associated with solid organ transplantation have also been reported, less commonly plasmoblastic lymphoma registers in immunocompetent patients. The disease is more common in male patients (75 %) aged from 8 to 62 years (median age 50 years), and most often the tumor lesions are localized in the oral cavity. Rare localizations of plasmoblastic lymphoma include pleura, testicles, mammary glands, lungs, and skin. As casuistic areas of lesions, the central nervous system can be noted.The article describes a clinical case of HIV-positive pediatric patient with rare plasmoblastic lymphoma of chiasmosellar zone. The disease was complicated with secondary hypocorticism and hypotyreosis, a deficiency of somatotrophic hormone and diabetes insipidus.